PENGARUH RELIGIUSITAS TERHADAP KINERJA PEGAWAI MELALUI NIAT WHISTLEBLOWING (Studi Pada Karyawan Badan Usaha Non Akademik Universitas Brawijaya) - Istiqomah Nur Frida; M. Cholid Mawardi; Hariri Hariri (Universitas Islam Malang, 2022)
Fraud is a latent danger that threatens the survival of an organization/company to the state. Efforts to minimize the risk of fraud (fraud) organizations implement various policies, one of which is through whistleblowing. The level of religiosity is one of the factors in a person's whistleblowing actions. The study aims to analyze the level of religiosity affect the intention of employees/employees in whistleblowing on employees of Non-academic business entities Brawijaya University. The method used is quantitative explanatory research method with a sample of 60 people from 220 employees in BUNA. The results of this study religiosity significantly affect the performance of employees. Religiosity has no significant effect on the intention of whistleblowing. Intention to do whistleblowing significantly affect employee performance. Whistleblowing intentions cannot mediate the influence between religiosity on employee performance at BUNA. The limitation of this study is the return of the research questionnaire that is not 100% that is only 75% of the distributed and the study only focuses on BUNA only so that the coverage is still less extensive. Research variables taken should be more varied, not just religiosity, whistleblowing, and employee performance. On the other hand, the suggestion that can be given to more researchers is that it is expected that more researchers can increase the observation period and add independent variables. In addition, further researchers were able to increase the number of respondents in the study and expand the scope of research.Keyword: Fraud, Profitability, Whistleblowing